Przygody barona Munchhausen - Gautier, Theophile, 1836-; Dore, Gustave, 1832-1883.; Hartwig, Julia (Warszawa : Wydawnictwa Artystyczne i Filmowe, 1991)
Polish translation of the fictional adventures of Munchausen who traveled and fought in the Turkish War of 1760. For ages 9-12.
Polish translation of the French version by Theophile Gautier, published under title: Aventures du Baron de Munchhausen.